More busy bees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Association Communautaire pour le Développement de Thionck Essyl, in Dakar, Senegal (fax: + 1 221 826 3155) writes to inform us of their refresher training course in bee-keeping, an area they have worked in for five years. They are keen to...